2020
DOI: 10.3390/medicina56100539
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Activated Cooling Vest’s Effect on Cooling Rate Following Exercise-Induced Hyperthermia: A Randomized Counter-Balanced Crossover Study

Abstract: Background and objectives: Exertional heat stroke (EHS) is a potentially lethal, hyperthermic condition that warrants immediate cooling to optimize the patient outcome. The study aimed to examine if a portable cooling vest meets the established cooling criteria (0.15 °C·min−1 or greater) for EHS treatment. It was hypothesized that a cooling vest will not meet the established cooling criteria for EHS treatment. Materials and Methods: Fourteen recreationally active participants (mean ± SD; male, n = 8; age, 25 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The decrease rate in Tre during post-exercise recovery in the FAN trial was 0.021 ± 0.002°C/min and did not significantly differ from that in the CON trial. This value is lower than the cooling rate recommended in the treatment of exertional heat stroke (0.15°C/min) as well as the rate obtained using a cooling vest (0.06 ± 0.02°C/min) ( 25 ). Differences observed in the above recommended values or the results of previous studies might be due to various factors related to the relationship between Ta and Tsk, skin surface area of the cooling and heat transfer occurring during recovery.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The decrease rate in Tre during post-exercise recovery in the FAN trial was 0.021 ± 0.002°C/min and did not significantly differ from that in the CON trial. This value is lower than the cooling rate recommended in the treatment of exertional heat stroke (0.15°C/min) as well as the rate obtained using a cooling vest (0.06 ± 0.02°C/min) ( 25 ). Differences observed in the above recommended values or the results of previous studies might be due to various factors related to the relationship between Ta and Tsk, skin surface area of the cooling and heat transfer occurring during recovery.…”
Section: Discussionmentioning
confidence: 61%
“…The decrease rate in Tre during post-exercise recovery in the FAN trial was 0.021 ± 0.002°C/min and did not significantly differ from that in the CON trial. This value is lower than the cooling rate recommended in the treatment of exertional heat stroke (0.15°C/min) as well as the rate obtained using a cooling vest (0.06 ± 0.02°C/min) (25). Differences The rectal (A), tympanic (B) and mean skin temperatures (C) under the CON and FAN trials.…”
Section: Discussionmentioning
confidence: 69%
“…A single dataset was extracted from 38 of the included studies [19,, with the remaining six studies yielding two datasets each [63][64][65][66][67][68]. These 50 datasets from 44 included studies reported findings from a total of 562 participants (461 male, 84 female, 17 sex not reported) who undertook passive cooling.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%